Prospect of Judicial Preview in the Constitutional Court Based on the Construction of Constitutional Law - Akmal, Diya Ul; Muin, Fatkhul; Karsa, Pipih Ludia (Jurnal Cita Hukum, 2020)
AbstractThe Constitutional Court is a state institution that has the authority for reviewing laws against the Constitution (Judicial Review). Several times in issuing its decisions, the Constitutional Court has acted as a Positive Legislator. The potential for a legal vacuum as the implication of revoking a law is large. and also the slow formation of laws by the legislative body (DPR) and the lack of quality of regulations. The current law-making does not pay attention to legal ideals based on Pancasila so that the resulting legal products lose their meaning. This has resulted in many people whose constitutional rights have been violated. The state should be present to give full constitutional rights to its citizens. The Constitutional Court needs additional authority to maintain the supremacy of the constitution. additional authority as a preventive mechanism is Judicial Preview. The French state places Judicial Preview as an authority of the Constitutional Council. Austria and Germany apply Judicial Preview as a preventive measure for losses that can occur if the Draft Law is passed. A renewal of the Constitutional Law to perfect existing ones makes the prospect of Judicial Preview in Indonesia an Urgency for immediate implementation.Keywords: Constitutional Court, Authority, Judicial Preview AbstrakMahkamah Konstitusi merupakan lembaga negara yang memiliki kewenangan pengujian Undang-Undang terhadap Undang-Undang Dasar (Judicial Review). Dalam mengeluarkan putusannya Mahkamah Konstitusi beberapa kali bertindak sebagai Positif Legislator. Potensi terjadinya kekosongan hukum sebagai implikasi dicabutnya suatu Undang-Undang sangatlah besar. Ditambah dengan lambatnya pembentukan Undang-Undang oleh lembaga legislatif (DPR) serta kualitas peraturan yang kurang. Pembuatan Undang-Undang saat ini tidak memperhatikan cita hukum yang berakar pada Pancasila sehingga produk hukum yang dihasilkan kehilangan maknanya. Hal ini mengakibatkan banyak masyarakat yang dilanggar hak konstitusionalnya. Negara seharusnya hadir untuk memberikan hak konstitusional secara penuh kepada warga negaranya. Untuk mencegah hal tersebut maka Mahkamah Konstitusi membutuhkan suatu kewenangan tambahan untuk menjaga tegaknya supremasi konstitusi. Kewenangan tambahan sebagai mekanisme preventif tersebut berupa Pengujian Rancangan Undang-Undang (Judicial Preview). Perancis menempatkan Judicial Preview sebagai kewenangan dari Constitutional Council. Austria dan Jerman juga memberlakukannya sebagai tindakan pencegahan. Pembangunan Hukum Konstitusi untuk menyempurnakan yang sudah ada menjadikan prospek Pengujian Rancangan Undang-Undang di Indonesia menjadi urgensi untuk segera diterapkan.Kata Kunci: Mahkamah Konstitusi, Kewenangan, Judicial Preview АннотацияКонституционный суд - это государственное учреждение, которое имеет право проверять законы на предмет соответствия Конституции. Вынося свои решения, Конституционный суд несколько раз выступал в качестве позитивного законодателя. Потенциал правового вакуума как последствия отмены закона огромен, особенно в сочетании с медленным формированием законов законодательным органом (DPR) и отсутствием качественных нормативных актов. Текущее формирование законодательства не обращает внимания на идеалы права, укоренившиеся в Pancasila, так что получаемые легальные продукты теряют свое значение. Это привело к тому, что конституционные права многих людей были нарушены. Государство должно присутствовать, чтобы предоставить своим гражданам полные конституционные права. Чтобы этого не произошло, Конституционному суду необходимы дополнительные полномочия для защиты верховенства конституции. Дополнительные полномочия в качестве превентивного механизма представлены в форме судебного предварительного надзора (Judicial Preview). Франция помещает судебный предварительный надзор в ведение Конституционного Совета. Австрия и Германия также приняли его в качестве меры предосторожности. Разработка Конституционного закона с целью усовершенствования существующего делает перспективу судебного надзора в Индонезии неотложной его реализацией.Ключевые Слова: Конституционный Суд, Власть, Судебный Надзор